Fertility and its proximate determinants in Bangladesh: Evidence from the 1993/94 demographic and health survey - M. Mazharul Islam; Abdullah Al Mamun; Radeshayam Bairagi (Asia-Pacific Population Journal, 1998)
Contraception plays the most prominent role in reducing fertility in Bangladesh.